Gradient vector fields which characterize warped products - Innami, Nobuhiro; Kim, Byung Hak (MATHEMATICA SCANDINAVICA, 2001)
We find what condition on gradient vector fields characterizes warped products, Riemannian products and round spheres. To do this we apply the theory of Jacobi equations without conjugate points to the differential maps of the local one-parameter groups generated by gradient vector fields.